2018
DOI: 10.1097/md.0000000000010857
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of fractional exhaled nitric oxide for asthma-chronic obstructive pulmonary disease overlap syndrome

Abstract: To examine the difference in the fractional exhaled nitric oxide (FeNO) between chronic obstructive pulmonary disease (COPD) patients with asthma-COPD overlap syndrome (ACOS) and patients with Non-ACOS COPD (Non-ACOS) and to investigate the correlation between FeNO levels and the differential cell counts of eosinophils in induced sputum, in order to explore the diagnostic value of FeNO in ACOS.A prospective, case-control study was performed on 53 cases of ACOS group and 53 cases of Non-ACOS group in the Respir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 26 publications
4
8
0
Order By: Relevance
“…In a different case-control study, the authors focused on 53 patients diagnosed as ACOS and 53 patients who were categorized as non-ACOS. Results of the study show that the ACOS group had significantly higher FeNO levels than non-ACOS group (37 ppb vs. 20 ppb; P-value < 0.01) [18]. These results are consistent with our findings of observing high FeNO levels in the patients with ACOS as compared to non-ACOS (28.19 ppb vs. 19.48 ppb) group (Table 1).…”
Section: Discussionsupporting
confidence: 86%
“…In a different case-control study, the authors focused on 53 patients diagnosed as ACOS and 53 patients who were categorized as non-ACOS. Results of the study show that the ACOS group had significantly higher FeNO levels than non-ACOS group (37 ppb vs. 20 ppb; P-value < 0.01) [18]. These results are consistent with our findings of observing high FeNO levels in the patients with ACOS as compared to non-ACOS (28.19 ppb vs. 19.48 ppb) group (Table 1).…”
Section: Discussionsupporting
confidence: 86%
“…This study also showed that the FeNO levels were positively correlated with the expression of the activation (CD66b, CD11b) and degranulation (CD66b, CD11b) markers for both leukocytes. This result is consistent with the results in the previous studies conducted by Guo et al [ 76 ] and Kobayashi et al [ 77 ], who also indicated that FeNO levels were reflected by eosinophilic airway inflammation [ 78 ]. In fact, the activated neutrophils can recruit the Th17/IL-17 and Th1 cells via chemokine release [ 79 ] and cause neutrophil infiltration within the airways [ 80 ].…”
Section: Discussionsupporting
confidence: 93%
“…Usually, there is a wide variety of reversible airflow limitations. The overall age of onset of asthma is earlier than COPD, usually with a good prognosis ( 24 , 25 ). It is associated with interactions such as allergies, airway inflammation, airway hyper-responsiveness, and neurological factors.…”
Section: Discussionmentioning
confidence: 99%